The Birth of Fluorescence from Thermally Polymerized Glycine. Issue 15 (6th May 2022) - Cossu, Franca Lucia; Poddighe, Matteo; Stagi, Luigi; Anedda, Roberto; Innocenzi, Plinio
Abstract: Thermal polymerization of glycine, the simplest amino acid bearing only one alfa carbon atom, is not an efficient process in mild conditions. Hydrothermal processing of glycine produces only small peptides, up to four units on average, with only a fraction of glycine that reacts. In the present work, boric acid is used as a catalyst to promote the formation of glycine polypeptides. The final product is characterized by an extended polymeric structure and an intense blue fluorescence characterizes the final product. A comparison with glycine reacted in hydrothermal conditions without the catalyst shows that boric acid plays a primary role in promoting the amidation reactions. The structure of the glycine polymers has been investigated by nuclear magnetic resonance, Fourier transform infrared and Raman spectroscopies, and the optical properties by UV–vis and fluorescence spectroscopies. The full reaction of glycine promoted by boric acid catalysis produces a disordered structure with loss of molecular conformations and blue emission. Abstract : Thermal polymerization of glycine catalyzed by boric acid results in the formation of polyglycine. The polypeptide is characterized by an extended polymeric structure and an intense blue fluorescence. The formation of fluorescent species in polyglycine is strictly correlated with the extension of the amidation.